Il Concilio Vaticano II «in dibattito» - Routhier, Gilles (Annali di studi religiosi, 2012)
The amount of discussion or tension observable in the Catholic Church during the post-conciliar period should not come as a surprise. In fact, these were already alive and acute during the Council. By making the word circulate freely and by listening, the Council actually permitted the disclosure of the tensions and debates already extant in the ecclesiastical corpus at least from the beginning of the second half of the 19th century onwards. These tensions mainly concern the relationship between the Catholic Church and modernity and, more in general, its relationship with the ‘others’.